Preaching Management from the Perspective of KH. Sholeh Bahruddin - Fauzul Rhohma Dhona Oktavianti; Anang Sholikhudin; Sopiyah; Tasya Indri Oktavia; Dina Khalimatus Sa’diyah (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2026)
From Kiai Sholeh's perspective, religion essentially serves as a guide and savior for his followers. This study aims to understand KH. M. Sholeh Bahruddin's views on religious tolerance and the practice of such tolerance. This type of research is a qualitative study using a phenomenological approach with primary and secondary data sources. Data collection techniques in this study include participant observation, in-depth interviews, and documentation analysis. The results of the study indicate that Kiai Sholeh's views on religious tolerance are practices of tolerance found in Sufism, which include the application of the Galak Gampil fiqh law, comforting behavior, and the application of other fiqh laws. This is reflected in his preaching with the principle of "hugging not hitting, seeking friends not enemies, inviting not mocking, and spreading affection not cursing" as well as adhering to the principle of socializing with non-Muslims, namely "there is no minority or majority society, there is only plurality" to all people without limiting ethnicity, religion, race, or culture. This attitude of tolerance includes a broad and confident attitude, namely the attitude of students who have broad views and a deep understanding of various sciences, both worldly and social sciences.